The Risk Assessment and Prediction Tool (RAPT) after Hip and Knee Replacement: A Systematic Review - Sconza, Cristiano; Respizzi, Stefano; Grappiolo, Guido; Monticone, Marco (Joints, 2019)
Purpose The Risk Assessment and Prediction Tool (RAPT) is an interesting instrument for predicting the discharge destination and length of stay (LOS) for patients after hip or knee arthroplasty. The aim of this review is to describe its predictive ability, current utilization, and future prospects through the analysis of scientific literature.Methods The databases of PubMed, Web of Sciences, Cochrane Library, and Pedro were searched for English studies on RAPT prediction capacity. Only original prospective or retrospective articles that analyze specifically the use of RAPT were included, whereas those concerned with other preoperative prediction tools or those only considering other aspects of recovery after joint replacements were excluded.Results A total of 27 references were retrieved, and 8 studies were selected. All analyzed studies demonstrated that RAPT could reduce LOS and accurately predict discharge disposition especially for high- and low-risk patients. In the intermediate risk category, a targeted intensive postoperative rehabilitation program has demonstrated good results in reducing the uncertain outcome.Conclusion Although contrarily to many of the other scores, the RAPT has been validated in multiple countries with relatively similar results between different institutions; however, its validity has yet to be tested and adapted in every nation context. Further studies confirming the predictive accuracy of RAPT at other institutions are needed as well as studies assessing the effect of using RAPT to identify patients for targeted interventions in terms of LOS, discharge disposition, clinical outcomes, and financial impact.Level of Evidence This is a level IV, systematic review of level III and IV study.
Keywords: Risk Assessment and Prediction Tool; joint replacement; joint arthroplasty